Enhancing the Entrepreneurial and Intrapreneurial Attributes of Engineering Graduates: A Review Proposal for Metallurgy and Materials Engineering Undergraduate Curricula at Two African Universities - Elias Matinde (MDPI AG, 2018)
This paper explores the potential opportunities to enhance the entrepreneurial and intrapreneurial attributes of graduates in the Metallurgy and Materials Engineering curricula at two universities in Zimbabwe and South Africa. Due to the diminishing geographical constraints between Zimbabwe and South Africa, and the strong juxtaposition between the two economies, this paper adopts a simplified comparative education methodology to benchmark education best practices between these two countries. While the reviewed curricula in their present form may be providing learners with opportunities for disciplinary problem solving and inquiry-based learning, this paper proposes a body-centred cubic (bcc) model to integrate a new dimension of entrepreneurial and intrapreneurial education into the teaching and learning space. Based on the 3D bcc lattice with six planes, where the first five planes represent the current curricula, pedagogy practices and desired attributes, the sixth plane is taken to represent the additional dimensions of the desired entrepreneurial and intrapreneurial attributes.